Early Detection Of Heart Attack After Cardiac Catheterization In Health Promotion Perspective: A Case Study - Ramli Muhammad; Syaifoel Hardy (Institute of Computer Science (IOCS), 2022)
Heart attack cases among cardiovascular disease continue increasing every year and ranking as the highest cause of death in Indonesia. The objective of this research was to provide a framework for health promotion nurses to prevent heart attacks after cardiac catheterization. This research used a case study with the Case Management Society of America (CMSA) model. The case was selected from a patient with Coronary artery disease (CAD), 58 years old, retired of a civil servant, ex-chronic smoker, controlled hypertension, and a family history of CAD. The stages of CMSA data processing include Assessment, Preparation Pre-Catheterization, Recovery Phase, Planning and Intervention, and Evaluation. Objective data was taken from the physical examination results. Subjective data were obtained from interviews according to the CMSA standard, reputed journals, and other official documents. Analysis of the case study was conducted by coding, categorizing, comparing, and organizing. This case study revealed that health promotion nurses need to know the potential complications of post-heart catheterization i.e. shortness of breath, chest pain, lack of activity that is not known by family members, assumptions about uncontrolled nutrition, irregular medication, and heart attacks. The research recommended to prevent heart attacks post catheterization, health promotion nurses have to provide daily notes as patient progress reports and set a regular follow-ups.